A Comprehensive Review on AI-Driven Healthcare Transformation - Balakrishna, Sivadi; Kumar Solanki, Vijender (Ingeniería Solidaria, 2024)
Introduction: In the dynamic landscape of healthcare, the intersection of cutting-edge technology and patient-centric solutions has sparked a paradigm shift, and at the forefront of this transformative wave is Artificial Intelligence (AI). Problem: Focusing on the multifaceted integration of AI technologies, the narrative explores their pivotal role in enhancing patient outcomes. Objective: This paper delves into the dynamic realm of healthcare transformation over the strategic exploitation of artificial intelligence (AI). Methodology: This paper explores the profound impact of AI on healthcare, examining the current state of the field and envisioning its future. From machine learning algorithms for early disease detection to personalized treatment plans, the paper delves into the diverse applications of AI in healthcare and the potential it holds for revolutionizing the entire ecosystem. From customized treatment strategies to streamlined healthcare processes, the paper unravels the diverse ways AI is reshaping the healthcare landscape. Results: The imperative to improve patient outcomes, characterized by enhanced efficiency, precision, and personalized care, finds a promising ally in AI. The paper has illuminated how AI technologies, including machine learning and advanced analytics, offer tangible solutions to longstanding challenges in diagnostics, treatment planning, and patient engagement. Conclusions: A comprehensive examination of emerging trends illuminates the potential for substantial improvements in patient well-being facilitated by the synergistic partnership of AI and healthcare practices. Originality: The exploration of AI’s applications throughout this paper underscores its transformative potential in reshaping traditional healthcare practices. Restrictions: The prospect of continually improving patient outcomes through innovative technologies remains at the forefront of this transformation.